Climate in tourism’s research agenda: future directions based on literature review - Hélder Lopes; Paula Remoaldo; Maurício Silva; Vitor Ribeiro; Javier Martín Vide (Boletín de la Asociación de Geógrafos Españoles)
One of the major challenges’ tourism faces today is climate change, which inevitably involves adjusting many destinations and tourists to new scenarios. For that, a literature review about the link between tourism and climate is mandatory. Therefore, the present paper aims to establish the evolution of the relationship between tourism and climate, since relevant studies were published from 1940 to 2020. A bibliometric analysis using qualitative and quantitative methods were used for measuring the coverage ratio of tourism and climate (change) in spatial-temporal studies. Web of Science (WoS) and Scopus databases were used to carry out an in-depth analysis based on 889 publications related to tourism climatology. These were synthesized in attributes and codes (e.g. location, journal name, geographic level, methods of analysis, results, implications, and trends). It is true that in the context of tourism research, themes and assumptions give or take a few exceptions, remain constant. Most of the 889 studies analyzed focused on climatological hotspots, such as impacts of climate change on tourism (28.4%) and urban and bioclimatic comfort of tourists in affected destinations (13.2%), with a lower coverage of tourism-related topics such as policies of climate change in tourism (6.1%) or strategies and concrete options to re-enable tourist destinations for climate change (0.2%). The research methods, procedures and results can contribute to advance tourism climatology to a new phase of theoretical and practical application for tourism planning.